Plano de negócio SP para 2 : plataforma jornalística para a curadoria de roteiros para casais - Souza, Clésio Henrique de Oliveira (2018)
This paper proposes a journalistic business model that explores the curation of tours for couples in São Paulo. The capital of São Paulo offers thousands of entertainment options for every type of people, but the robust network of establishments can prove to be too complex even for locals looking for a fun option. This public, despite having an interest in consuming, may end up giving up enjoying this universe due to the immensity of choices that need to be made. On the other hand, establishments lack a hub in search of alternatives to get to know their audience better and generate a stable flow of customers, even at less favorable times. In this way, this work analyzes how couples living in the city behave when selecting tours and proposes a product marketing strategy. The methodological part of the research included theoretical revision on the current journalistic market, information curation, creation of value and founding. In addition, it includes a quantitative research with the target audience and a qualitative research with specialists of diverse areas (journalism, digital marketing, branding and administration). A business plan was developed that seeks to create unique experiences for these couples of all genres in São Paulo. The project demonstrates economic and financial viability (IRR of 51.3% and NPV of R$ 1,354,189.51) and associated risks. This project appears in a moment of deep transformations in the information universe, coming from the internet. Therefore, its main objective is to contribute to the planning of new journalistic businesses, in a scenario in which journalism, marketing and administration are increasingly close.